"Wrong Way Up": Temporal and Spatial Dynamics of the Networks for Body Motion Processing at 9.4 T. (10th July 2017) - Pavlova, Marina A; Erb, Michael; Hagberg, Gisela E; Loureiro, Joana; Sokolov, Alexander N; Scheffler, Klaus
Abstract: Body motion delivers a wealth of socially relevant information. Yet display inversion severely impedes biological motion (BM) processing. It is largely unknown how the brain circuits for BM are affected by display inversion. As upright and upside-down point-light BM displays are similar, we addressed this issue by using ultrahigh field functional MRI at 9.4 T providing for high sensitivity and spatial resolution. Whole-brain analysis along with exploration of the temporal dynamics of the blood-oxygen-level-dependent response reveals that in the left hemisphere, inverted BM activates anterior networks likely engaged in decision making and cognitive control, whereas readily recognizable upright BM activates posterior areas solely. In the right hemisphere, multiple networks are activated in response to upright BM as compared with scarce activation to inversion. With identical visual input with display inversion, a large-scale network in the right hemisphere is detected in perceivers who do not constantly interpret displays as shown the "wrong way up." For the first time, we uncover (1) (multi)functional involvement of each region in the networks underpinning BM processing and (2) large-scale ensembles of regions playing in unison with distinct temporal dynamics. The outcome sheds light on the neural circuits underlying BM processing as an essential part of the social brain.